2006
DOI: 10.1074/jbc.m609321200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of FBP11 WW1-PL Ligand Complex Reveals the Mechanism of Proline-rich Ligand Recognition by Group II/III WW Domains

Abstract: FBP11/HYPA is a mammalian homologue of yeast splicing factor Prp40. The first WW domain of FBP11/HYPA (FBP11 WW1) is essential for preventing severe neurological diseases such as Huntington disease and Rett syndrome and strongly resembles the WW domain of FCA, the essential regulator for flowering time control. We have solved the structure of FBP11 WW1 and a Pro-Pro-Leu-Pro ligand complex, and demonstrated the binding mechanism with mutational analysis using surface plasmon resonance. The overall structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Our results show that the two WW domains of FBP21 both recognize peptides containing PPR, PPLP, as well as PPPP motifs. We also found that the binding interfaces on both WW domains involve both the XP and XP2 grooves, similar to what has been reported for group II domains (49,50). In conclusion, WW domains of group II and group III cannot be clearly differentiated based on their three-dimensional structure, binding interface, and ligand specificity and should be viewed as a single group.…”
Section: Discussionsupporting
confidence: 87%
“…Our results show that the two WW domains of FBP21 both recognize peptides containing PPR, PPLP, as well as PPPP motifs. We also found that the binding interfaces on both WW domains involve both the XP and XP2 grooves, similar to what has been reported for group II domains (49,50). In conclusion, WW domains of group II and group III cannot be clearly differentiated based on their three-dimensional structure, binding interface, and ligand specificity and should be viewed as a single group.…”
Section: Discussionsupporting
confidence: 87%
“…The bipartite mode of the PP1 and PP3 moieties in Htt-PRR and the tandem WW domains in HYPA significantly enhance their binding affinity. The first WW domain of HYPA is well ordered (29,(35)(36)(37), whereas it may have a chaperoning effect on the folding of the secondary WW domain. Our results indicate that the two WW domains work as a unit to interact with Htt-PRR.…”
Section: Bipartite Interaction Between Prr Of Htt and 2ww Of Hypa-mentioning
confidence: 99%
“…28,29 By contrast, group II and III WW domains have an additional groove, XP2, which is formed by the conserved tyrosine and an aromatic residue in β2 strand. 33,34 In this respect, groups II and III are more similar to SH3 domains, which have two successive XP grooves, suggesting that these structurally and evolutionary unrelated protein modules have converged on a similar mechanism for polyproline recognition. Based on the distinct structural features and similar binding specificities of group II and III WW domains, including recognition of uninterrupted polyproline sequences (PPPPP) in addition to PL and PR motifs, it was recently proposed that these groups be merged into a larger class II/III.…”
Section: Introductionmentioning
confidence: 98%